Investing digital marketing tools in supporting the quality of education: an application study in the Wasit Education Directorate - Abdulraheem Y. O. AL Abdiy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Through an applied study in the Wasit Education Directorate, this study seeks to investigate how investing in digital marketing tools supports educational quality. Given the rapid pace of digital transformation, educational institutions now need to implement digital strategies that improve communication between parents and students and aid in the learning process. Through semi-structured interviews with educators, experts, students, and parents, the study employed a qualitative curriculum. The findings demonstrated that digital marketing tools improve education quality by fostering communication, encouraging participation, and offering interactive content. Numerous issues were also brought to light by the study, including inadequate infrastructure and a dearth of training in digital marketing, and suggested creating consistent digital tactics to facilitate the fusion of digital marketing and education.